Sistem Informasi Manajemen: Pilar Penting dalam Organisasi Modern - Windi Nandina; Rayyan Firdaus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Management Information System (MIS) is a crucial component in modern organizations that aims to integrate data from various sources to support effective and efficient decision-making. This article discusses the definition, components, and key functions of a SIM, as well as its application in various industries such as manufacturing, healthcare, and finance. In addition, the article also identifies challenges faced in SIM implementation, such as high costs, employee training needs, resistance to change, and data security issues. A case study at XYZ company shows the significant benefits of SIM implementation, including improved operational efficiency and product quality. With the development of technologies such as artificial intelligence, machine learning, and big data, the future of SIM looks increasingly bright, offering great potential to improve organizational efficiency and competitiveness. This article emphasizes the importance of continued investment in SIM to ensure relevance and competitiveness in the global market.